Measurement of Organic Catfish Supply Chain With Supply Chain Operation Reference (SCOR) Approach In The Home Industry (Organic Catfish In Dungus Sidoarjo) - Prasetyo, Waluyo; Nita Kusuma Wati; Rina Sri Wulandari (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2021)
Ready to serve food is food that has been cooked and stored, either using preservatives or by various storage methods. The object of this research is a producer of catfish frozen food in Sidoarjo. The limited yield of catfish from this business is due to the inadequate capacity of the pond and it only produces 2,000 catfish per harvest period. This organic catfish business still has not implemented a structured supply chain system; performance measurement has been focused on each business owner. The aim of this research was to measure the supply chain of organic catfish using the SCOR approach. It can be concluded that by selecting Supplier A will resolve the problem. Based on the 19 performance indicators, there were three marked red indicators in the Traffic Light System that were needed to be improved.